Application of Blue Light (Red-Free) Angiography Using Confocal Scanning Laser Ophthalmoscope. Issue 10 (October 2015) - Hua, Rui; Yao, Kai; Chen, Lei; Li, Jun
Abstract : We introduced the application of blue light (red-free) angiography, which may significantly improve the current knowledge and application of angiography in ophthalmology. We enhanced the image quality of red-free angiography through the use of fluorescein sodium. Compared with fluorescein angiography, the red-free angiography, in which the filter is not required, can generate the fundus images with more information.